2020
DOI: 10.3390/electronics9060973
|View full text |Cite
|
Sign up to set email alerts
|

Design, Dynamics Analysis, and Real-Time Stiffness Control of a Variable Stiffness Joint

Abstract: This paper proposes a variable stiffness joint based on a symmetrical crank slider mechanism (SCM-VSJ). Firstly, the mechanical design and the working principle of the variable stiffness joint is described, and its stiffness regulation characteristics are studied. Secondly, the dynamical model of variable stiffness joint including joint motor, harmonic reducer and stiffness adjustment motor is established, in addition, the transmission mechanism of the crank slider mechanism and the elastic deformation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The VSJ using leaf springs was proposed by Yang et al The effective length of the spring can be changed by a crank-slider mechanism to achieve a wide range of stiffness variatio. 13 Wu et al 14 combined cams and leaf springs to realize a VSJ that can be combined with one or more leaf springs, and the stiffness range of the joint is determined by the number of springs used.…”
Section: Introductionmentioning
confidence: 99%
“…The VSJ using leaf springs was proposed by Yang et al The effective length of the spring can be changed by a crank-slider mechanism to achieve a wide range of stiffness variatio. 13 Wu et al 14 combined cams and leaf springs to realize a VSJ that can be combined with one or more leaf springs, and the stiffness range of the joint is determined by the number of springs used.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [17] proposed a new general stiffness model, which includes linear and nonlinear stiffness models, for serial mechanisms. Yu et al [18] calculated and analyzed the dynamic stiffness of a symmetrical crank slider mechanism with a variable-stiffness joint. Lu et al [19] suggested a new method for calculating the stiffness of bolted connectors and analyzed the effects of joint surface stiffness on the overall stiffness.…”
Section: Introductionmentioning
confidence: 99%